2017
DOI: 10.1097/yct.0000000000000405
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Global Variability in Electroconvulsive Therapy Utilization

Abstract: These findings suggest that across the globe ECT but not antidepressant medication utilization is associated with the degree to which a nation financially invests in mental health care for its citizens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…If the TPR for ECT in other (geographical) European countries are taken as comparative values, it becomes apparent that Switzerland is in the lower midfield in terms of ECT patients (Table 2). As this selective sample on TPR makes clear, strong variations in patient treatment rates are evident 33 . These differences also extend at the global level, not only in terms of patient utilization rates, but also in terms of ECT application, administration, and practice.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…If the TPR for ECT in other (geographical) European countries are taken as comparative values, it becomes apparent that Switzerland is in the lower midfield in terms of ECT patients (Table 2). As this selective sample on TPR makes clear, strong variations in patient treatment rates are evident 33 . These differences also extend at the global level, not only in terms of patient utilization rates, but also in terms of ECT application, administration, and practice.…”
Section: Discussionmentioning
confidence: 84%
“…As this selective sample on TPR makes clear, strong variations in patient treatment rates are evident. 33 These differences also extend at the global level, not only in terms of patient utilization rates, but also in terms of ECT application, administration, and practice. Switzerland and countries with comparable TPRs also rank in the lower middle range in a global comparison-the average TPR worldwide is estimated to be 23.4 persons treated per 100,000 population.…”
Section: Application Of Ect In International Comparisonmentioning
confidence: 99%
“…In a study comparing published rates of ECT and antidepressant medication utilization across nations, and the impact of health, social, and economic indices, Rakita et al found that government expenditure on mental health was the only significant contributor to global variation in ECT use worldwide, while the Human Development Index, a composite index of life expectancy, education rates, and per capita income indicators, significantly correlates with global antidepressant utilization. 27 These findings suggest that across the globe, ECT, and as an extension, other Interventional Psychiatric approaches that also require equipment and multiple personnel for delivery, can be a bellwether measure of the degree to which a nation financially invests in mental health care for its citizens. Although there are no population data available on rTMS utilization across Canada, the ability to access this Health Canada approved treatment varies by province as a function of whether it is publicly funded.…”
Section: Funding/advocacymentioning
confidence: 99%
“…Moreover, in a recent large observational study of older patients, ECT was associated with a lower one-year all-cause mortality and reduced suicide rates during three months after treatment [ 8 ]. Despite the consistent evidence that ECT is an effective treatment for patients with TRD, research suggest that it is underutilised [ 9 11 ]. This is partly due to limited availability of ECT, patient choice, stigma and a dated perception of the treatment [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the consistent evidence that ECT is an effective treatment for patients with TRD, research suggest that it is underutilised [ 9 11 ]. This is partly due to limited availability of ECT, patient choice, stigma and a dated perception of the treatment [ 9 11 ]. It is also due to the fact that maintenance ECT (M-ECT) might be required, a practice that is uncommon in England [ 12 ] and not supported by UK National Institute for Health and Care Excellence (NICE) as routine treatment [ 13 ].…”
Section: Introductionmentioning
confidence: 99%